Gerakan Cegah Hipertensi melalui Pemeriksaan Tekanan Darah dan Konseling Kesehatan - Rismanudin Rismanudin; Suparman Suparman; Indiriadi Indiriadi; Muhammad Evendi Halulanga; Ernawati Ernawati; Cicci Chairunisa Masum; Fani Fionita; Wahyuni Wahyuni; Wiwiek Hidayati Jaya (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Hypertension is a major public health problem that often occurs without symptoms and may cause serious complications such as stroke, heart disease, and kidney failure. Low awareness of regular blood pressure monitoring contributes to delayed detection and treatment. Objective: This community service program aimed to improve public knowledge regarding hypertension, conduct early detection through blood pressure screening, and encourage healthy lifestyle practices. Method: The program used promotive, preventive, educational, and direct screening approaches among adults and older adults. Activities included registration, pre-test, blood pressure examination, health education, individual counseling, post-test, and program evaluation. Result: The program involved 65 participants consisting of 40 women and 25 men. Blood pressure examination showed that 43.1% had normal blood pressure, 30.8% were pre-hypertensive, and 26.1% had grade 1–2 hypertension. Participants demonstrated improved understanding of hypertension prevention and expressed willingness to adopt healthier lifestyles. Conclusion: Blood pressure screening and health counseling effectively improved early detection, knowledge, awareness, and healthy lifestyle behaviors related to hypertension prevention.